Factores familiares y el comportamiento en el aula en estudiantes de secundaria de la Institución Educativa Elzeario Mac Donald, Pebas 2024 - Yovera Monteza, María Cruz (2025)
The purpose of this research was to analyze the relationship between family factors and classroom behavior of high school students at the Elzeario Mac Donald Educational Institution, Pebas, in the year 2024. To do this, a quantitative approach was adopted, and a relational study was developed with a non experimental design and a correlational scope. The population was made up of 99 high school students, to whom the observation technique was applied using a structured guide, previously validated by three specialists in the field. The reliability of the instrument was determined through the item intercorrelation method, using Cronbach's Alpha coefficient. The results obtained from Kendall's Tau-b correlation analysis showed a coefficient of 0.657, with a bilateral significance of 0.05. This reflected a moderately high relationship between family factors and classroom behavior, which allowed us to conclude that those students from homes with a stable family structure and a favorable environment showed more positive attitudes and better performance in the classroom. In contrast, those who grew up in less structured family environments or with unfavorable dynamics presented greater difficulties in their school behavior.